Advantages of Widefield Optical Coherence Tomography in the Diagnosis of Retinopathy of Prematurity - Nguyen, Thanh-Tin P.; Ni, Shuibin; Khan, Shanjida; Wei, Xiang; Ostmo, Susan; Chiang, Michael F.; Jia, Yali; Huang, David; Jian, Yifan; Campbell, J. Peter (Frontiers in Pediatrics, 2022)
Recent advances in portable optical coherence tomography (OCT) and OCT angiography (OCTA) have resulted in wider fields of view (FOV) and shorter capture times, further expanding the potential clinical role of OCT technology in the diagnosis and management of retinopathy of prematurity (ROP). Using a prototype, handheld OCT device, retinal imaging was obtained in non-sedated infants in the neonatal intensive care unit (NICU) as well as sedated infants in the operating room of Oregon Health & Science University (OHSU) Hospital. In this observational study, we provide an overview of potential advantages of OCT-based disease assessment in ROP. We observed that next-generation OCT imaging a) may be sufficient for objective diagnosis and zone/stage/plus disease categorization, b) allows for minimally-invasive longitudinal monitoring of disease progression and post-treatment course, c) provides three-dimensional mapping of the vitreoretinal interface and d) with OCTA, enables dye-free visualization of normal and pathologic vascular development.